Keeping what real? Vinyl records and the future of independent culture. (August 2019) - Palm, Michael
The revived popularity of vinyl records in the United States provides a unique opportunity for 'rethinking the distinction between new and old media'. With vinyl, the new/old dichotomy informs a more specific opposition between digital and analog. The vinyl record is an iconic analog artifact whose physical creation and circulation cannot be digitized. Making records involves arduous craft labor and old-school manufacturing, and the process remains essentially the same as it was in 1960. Vinyl culture and commerce today, however, abound with digital media: the majority of vinyl sales occur online, the download code is a familiar feature of new vinyl releases, and turntables outfitted with USB ports and Bluetooth are outselling traditional models. This digital disconnect between the contemporary traffic in records and their fabrication makes the vinyl revival an ideal case example for interrogating the limitations of new and old as conceptual horizons for media and for proffering alternative historical formulations and critical frameworks. Toward that end, my analysis of the revitalized vinyl economy in the United States suggests that the familiar (and always porous) distinction between corporate and independent continues to offer media studies a more salient spectrum, conceptually and empirically, than new-old or analog-digital. Drawing on ethnographic research along vinyl's current supply chain in the United States, I argue that scholars and supporters of independent culture should strive to decouple the digital and the analog from the corporate, rather than from one another. The pressing question about the future of vinyl is not, will there continue to be a place for analog formats alongside the digital; but rather, to what extent can physical media circulate independently of the same corporate interests that have come to dominate popular culture in its digital forms?